Identification of EOMES-expressing spermatogonial stem cells and their regulation by PLZF - Sharma, Manju; Srivastava, Anuj; Fairfield, Heather E; Bergstrom, David; Flynn, William F; Braun, Robert E (eLife, 2019)
Long-term maintenance of spermatogenesis in mammals is supported by GDNF, an essential growth factor required for spermatogonial stem cell (SSC) self-renewal. Exploiting a transgenic GDNF overexpression model, which expands and normalizes the pool of undifferentiated spermatogonia between Plzf +/+ and Plzf lu/lu mice, we used RNAseq to identify a rare subpopulation of cells that express EOMES, a T-box transcription factor. Lineage tracing and busulfan challenge show that these are SSCs that contribute to steady state spermatogenesis as well as regeneration following chemical injury. EOMES+ SSCs have a lower proliferation index in wild-type than in Plzf lu/lu mice, suggesting that PLZF regulates their proliferative activity and that EOMES+ SSCs are lost through proliferative exhaustion in Plzf lu/lu mice. Single cell RNA sequencing of EOMES+ cells from Plzf +/+ and Plzf lu/lu mice support the conclusion that SSCs are hierarchical yet heterogeneous.
Keywords: spermatogonial stem cells; PLZF; EOMES